Evaluation of effectiveness technological process of water purification exemplified on modernized Water Treatment Plant at Otoczna = Ocena efektywności procesów technologicznych uzdatniania wody na przykładzie zmodernizowanej Stacji w Otocznej - Jordanowska, Joanna; Jakubus, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the work of the Water Treatment Plant in the town of Otoczna, located in the Wielkopolska province, before and after the modernization of the technological line. It includes the quality characteristics of the raw water and treated water with particular emphasis on changes in the quality indicators in the period 2002 - 2012 in relation to the physicochemical parameters: the content of total iron and total manganese, the ammonium ion as well as organoleptic parameters (colour and turbidity).
Keywords: woda podziemna; odmanganianie; usuwanie żelaza; stacja uzdatniania wody; fizykochemiczne parametry wody do picia; organoleptyczne parametry wody do picia; groundwaters; purification water; manganese removal process; physicochemical parameters of drinking water; organoleptic parameters of drinking water